Intraperitoneal instillation of Ropivacaine for postoperative analgesia in laparoscopic cholecystectomy - Prasai, Adim; Prasai, Abha (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Laparoscopic cholecystectomy is one of the most frequently performed elective surgical procedures. Post-operative pain has been reported to be seen in 35-63% of patients undergoing laparoscopic surgeries. Use of intraperitoneal ropivacaine has been widely advocated in various minimal access abdominopelvic surgeries with satisfactory results. Laparoscopic cholecystectomy is a common surgical procedure in our hospital and pain is complained by the patients time and again in the postoperative period especially in the first 24 hours. Method: A cross sectional descriptive study was conducted in Nepal Medical College and Teaching Hospital among 129 patients. Patients(male/female) aged 18-65 years who were given ropivacaine intraperitoneally during laparoscopic cholecystectomy were included for the study. The post-operative analgesic effect of ropivacaine, a long-acting local anaesthetic agent was assessed. Result: Total number of female cases was 87 (67.4%) and male cases was 42 (32.6%). One hundred and fifteen (89.1%) patients fell in American Society of Anesthesiologist(ASA) physical status classification I and remaining 14 (10.9%) in American Society of Anesthesiologist (ASA)physical status classification II. Normal Body Mass Index(BMI) was seen in 89 (69%) patients whereas 1 (0.8) patient was underweight and 39 (30.2) patients were overweight. Visual Analog Scale(VAS) more than 4 was seen mostly at 8 hours. Adverse effect in postoperative period was seen in 11 patients. Among which 4 (36.3%) patients had tachycardia and PONV was seen in 7 (63.6%) patients. Conclusion: The instillation of bupivacaine and ropivacaine intraperitoneally was an effective method of postoperative pain relief in LC. It provided good analgesia in immediate postoperative period with ropivacaine, providing longer duration of analgesia.